Advancing antiracist research: addressing health inequities among juvenile legal system-impacted youth using Public Health Critical Race Praxis - Emily Dauria; Johanna Folk; Sarah Godoy; Evan Holloway; Jeanne McPhee; David Hoskins; Ali Yurasek; Katharine Galbraith; Sheridan Sweet; Eraka Bath; Marina Tolou-Shams (Health & Justice)
Abstract Youth impacted by the juvenile legal system (JLS) disproportionately experience health and healthcare inequities, including those related to substance use, mental health, and sexual and reproductive health. Structural racism is a primary driver of JLS systems contact and health inequities, interacting with other forms of oppression to negatively impact minoritized youth at every step of the JLS process. Despite the growing unmet need for tailored, empirically-driven programmatic and policy solutions, research focused on this multiply marginalized group often fails to explore or address racism as a factor shaping these inequities and identifying relevant health solutions. We use the Public Health Critical Race Praxis to offer recommendations for improving data collection and quality in longitudinal research addressing health inequities among JLS-impacted youth and families. Recommendations stem from a team of federally funded researchers and clinicians representing different career development stages, training backgrounds, and lived experiences, all of whom are working to address health inequities. Given the challenges JLS-impacted youth face and the significant need for rigorous research illuminating their health outcome and service needs, clinical and translational researchers would benefit from guidance on how to apply antiracist principles and research strategies to successfully engage JLS-impacted youth and families in longitudinal studies.